Seleção de leveduras não Sachharomyces para produção de cervejas especiais - Marina Perbone Leon (2020)
The craft and special beer market warming has boosted the search for novelty, specially the development of distinct products regarding its sensory features. The yeasts strains used in the majority of brewing belong to Saccharomyces genera, especially S. cerevisiae. However, wild non Saccharomyces yeasts are able to produce a wide range of flavour compounds that can be used in order to improve the flavour of these products. This work aims to characterize and select non Saccharomyces yeasts with potential for the production of special beers. Candida, Dekkera/Brettanomyces, Hanseniaspora, Meyerozyma, Pichia, Scheffersomyces, Spathaspora, Starmerella, Torulaspora, Wickerhamomyces, Zygossacharomyces and Zygotorulaspora yeasts were evaluated regarding their physiological and fermentative profiles and metabolite production. After maltose fermentation, stress tolerance and H2S production assays, four Starmerella meliponinorum and three Torulaspora delbrueckii yeasts were regarded as promising for beer production. These yeasts were, then, submitted to a bench scale fermentation assay. One S. meliponinorum and three T. delbrueckii were selected for 40 L pilot scale beer production. The resulting beers were as accepted as the beer produced with commercial reference S. cerevisiae yeast. Volatile compound profile for each beer was determined with gas chromatography. Beers fermented with cultures containing S. meliponinorum strain showed higher levels of ethyl octanoate (pineapple like flavour) in comparison with beer fermented with commercial S. cerevisiae yeast. T. delbrueckii strains showed higher fusel alcohol production than commercial S. cerevisiae. This study showed that the wild yeasts evaluated can be used in brewing, but industrial fermentation adaptation steps can improve reproductibility of the final product.